Very small size proteoliposomes abrogate cross-presentation of tumor antigens by myeloid-derived suppressor cells and induce their differentiation to dendritic cells. Issue 1 (11th March 2014) - Fernández, Audry; Oliver, Liliana; Alvarez, Rydell; Hernández, Arletty; Raymond, Judith; Fernández, Luis E; Mesa, Circe
Abstract : Background: Myeloid-derived suppressor cells (MDSCs) are among the major obstacles that adjuvants for cancer vaccines have to overcome. These cells cross-present tumor-associated antigens (TAA) to naive T lymphocytes with a tolerogenic outcome. Very Small Size Proteoliposomes (VSSP) is used as adjuvant by four therapeutic cancer vaccines currently in Phase I and II clinical trials. We previously found that VSSP reduces the suppressive function of MDSCs, then activating antigen-specific CTL responses in tumor-bearing (TB) mice, with the consequent reduction of tumor growth. However the mechanistic explanation for the immunomodulatory effect of this adjuvant in TB hosts has not been addressed before. Methods: TB mice were inoculated with VSSP and MDSCs isolated and characterized by their expression of Arg1 and Nos2 genes by RT-PCR. The effect of VSSP on antigen cross-presentation by MDSCs, regulatory T cells (Tregs) expansion and MDSCs differentiation towards dendritic cells (DCs) was analyzed by FACS. Student's t test or ANOVA and Tukey's tests were used for statistical analyses. Results: After inoculating VSSP into TB mice, a significant reduction of Arg1 and Nos2 gene expression was observed in recovered MDSCs. Concurrently the ability of these cells to induce down-regulation of CD3ζ chain on T cells was lost. Likewise in mice inoculated with the adjuvant lower percentages of Tregs were detected. In vitro, VSSP treatment was enough to differentiate MDSCs into phenotypically mature DCs, eliminating the former suppressive effect. Noteworthy, in vivo administration of VSSP to OVA-expressing (EG.7) TB mice abrogated this model antigen cross-presentation by splenic MDSCs. Similar results were obtained even when OVA antigen was administered into these TB mice formulated in VSSP. On the contrary, immunization with the same protein in polyI:C did not change the percentage of MDSCs expressing SIINFEKL/H-2K b complexes, whereas a concomitant injection of VSSP aborted the limitations of polyI:C in this setting. Conclusions: Altogether, these results indicate that VSSP has the peculiar capacity of inhibiting TAA cross-presentation and certain suppressive mechanisms on MDSCs which in turn, combined with the ability to induce differentiation of these cells into antigen-presenting cells (APCs), sustains this adjuvant as an ideal immunomodulator for cancer immunotherapy.